An Evaluation of the Causes, Impact and Perceptions about Abandoned Public Funded Projects in Ghana - Joseph Teye I. Buertey; Felix K. Atsrim; Kwasi Boateng; Richard Brace; Lord Aaron (Current Approaches in Engineering Research and Technology Vol. 6, 2024)
The construction industry is a key driver of every economy, and the successful implementation of developmental projects enhances the socio-economic wellbeing of the citizenry. In Ghana, however, abandoned projects have become a menace, affecting various sectors of the economy such as employment, housing, healthcare, education, and infrastructure. The objective of this chapter was to evaluate the perceptions, causal factors, and effects of project abandonment in the Ashanti region of Ghana. The research is quantitative in nature, drawing samples purposively from eighty (80) questionnaires self-administered to the general public, contractors, and staff of MMDAs, with a response rate of 75%. The study revealed that the major causes of project abandonment are poor project planning, challenges in client cashflow, and a lack of political goodwill due to changes in government. The research established that even though most projects initiated by the MMDAs are completed as challenged projects, huge national investments are left at the mercy of the weather when there is a change in government. These abandoned projects lead to huge sunk costs, the loss of economic activities, and a denial of the socio-economic benefits that are expected to be accrued from the project. It is recommended that modeling a reduction in project abandonment would require effective planning and procurement, improving funding mechanisms, and adopting a national developmental plan that would compel succeeding governments to continue with existing projects they inherit to avoid huge national losses.